BIMBINGAN KELOMPOK ONLINE DENGAN TEKNIK DISKUSI UNTUK KETERAMPILAN SOSIAL RENDAH - Putri Damayanti; Heris Hendriana; Tita Rosita (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
This study aims to find out the description of online group guidance with discussion techniques through zoom meetings for students who have low social skills. The method used is descriptive qualitative. This research uses analysis with an inductive approach where the data in this study is descriptive data which is generally in the form of words and pictures. Data collection tools using data triangulation, namely interviews, observations and documentation. The subjects of this study were students of class XI in Vocational High School, the subjects in this study were 2 people who were indicated to have low social skills. Based on the results of the study, it showed the application of online group guidance with discussion techniques through zoom meetings on students' social skills, when the initial service was implemented, students looked enthusiastic and responded well to activities so that the service implementation was completed. The response shown by students in group guidance activities through discussion techniques indicated that students have low social skills, it was found that the application of discussion techniques in online group guidance through zoom meetings was quite effective.Keywords: Social Skills, Discussion Techniques, Online Group Guidance